ANALISIS PENGUKURAN BEBAN KERJA FISIK DAN MENTAL PERAWAT MENGGUNAKAN INDEX OF PHYSICAL WORKLOAD DAN NASA-TASK LOAD INDEX SEBAGAI STRATEGI DALAM SELEKSI DAN PENEMPATAN PERAWAT - Nur Faizah; Muhardi Muhardi; Sri Suwarsi (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aimed to analyze the measurement of nurses' physical and mental workload using the Index of Physical Workload and the NASA-Task Load Index (NASA-TLX) as a strategy for selection and placement. The research method used in this study is a quantitative descriptive method, using a total sampling of 47 nurses in the Instalasi Rawat Intensif (IRI). The results showed that the physical workload of nurses was 23.38 (medium category), and the mental workload of nurses was 58.02 (high category). Strategies for selecting and placing nurses in the future include detailed and comprehensive job analysis, selection and placement of nurses according to qualifications, ergonomics programs, implementing fitness programs, following and understanding SOPs well, and enhancing cooperative relations with educational institutions.